2007
DOI: 10.1002/jbm.a.31169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of yield damage on the viscoelastic properties of cortical bone tissue as measured by dynamic mechanical analysis

Abstract: We have previously shown, using Dynamic Mechanical Analysis (DMA), that the presence of a defect in cortical bone tissue affects the apparent viscoelastic properties of that bone. However, mechanically induced damage is more complex than a machined defect making it difficult to predict its effect on bone viscoelasticity. We performed DMA measurements before and after introduction of yield damage into cortical bone beams from sheep radii. The specimens were placed in a DMA machine and baseline measurements of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
(64 reference statements)
4
14
0
Order By: Relevance
“…Previous studies have shown that the viscous nature of bone depends on hydration condition of the tissue (Yamashita et al, 2002), and such viscoelastic properties as storage modulus and loss modulus of bone increase with increasing damage density (Yeni et al, 2004; Yeni et al, 2007). In this study, a much higher total stress relaxation (Δσ) and a slightly greater time constant (τ) were observed in compression than in tension (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the viscous nature of bone depends on hydration condition of the tissue (Yamashita et al, 2002), and such viscoelastic properties as storage modulus and loss modulus of bone increase with increasing damage density (Yeni et al, 2004; Yeni et al, 2007). In this study, a much higher total stress relaxation (Δσ) and a slightly greater time constant (τ) were observed in compression than in tension (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ultimate displacement (Δ u ), the maximum displacement traveled by the cross-head before specimen’s failure, and work to fracture (W), the total amount of work done for fracture, were obtained as measures of structural ductility. Also, post-yield energy (W py ) was estimated as a ductility measure, where yield point was found using 5% secant stiffness method [25]. In order to assess the variation of structural ductility measures relative to strength, W py , W and Δ u were normalized with strength to produce post-yield energy to strength ratio (W py /F max ), work to fracture to strength ratio (W/F max ) and ultimate displacement to strength ratio (Δ u /F max ).…”
Section: Methodsmentioning
confidence: 99%
“…The post-yield behavior of bone is usually associated with microdamage accumulation (Forwood and Parker, 1989; Burr et al, 1997, 1998; Fazzalari et al, 1998a, b; Norman et al, 1998; Reilly and Currey, 1999; Timlin et al, 2000; Akkus and Rimnac, 2001), viscoelastic responses (Bredbenner and Davy, 2006; Joo et al, 2007; Yeni et al, 2007), and plastic deformation (Fondrk et al, 1988). For instance, yielding coincides with the formation of damage in bone (Zioupos et al, 1994), and the induced damages may lead to an elevated viscoelastic response of bone (Yeni et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, yielding coincides with the formation of damage in bone (Zioupos et al, 1994), and the induced damages may lead to an elevated viscoelastic response of bone (Yeni et al, 2007). In addition, microdamage accumulation plays a significant role in energy dissipation in both fatigue and monotonic fractures of bone (Schaffler et al, 1995; Burr et al, 1997; Jepsen and Davy, 1997; Martin et al, 1997; Fazzalari et al, 1998a, b; Norman et al, 1998; Vashishth et al, 1997, 2003; Zioupos, 2001).…”
Section: Introductionmentioning
confidence: 99%